2014
DOI: 10.1016/j.addr.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging techniques for nano-pathophysiology and theranostics

Abstract: The advent of nanoparticle DDSs (drug delivery systems, nano-DDSs) is opening new pathways to understanding physiology and pathophysiology at the nanometer scale. A nano-DDS can be used to deliver higher local concentrations of drugs to a target region and magnify therapeutic effects. However, interstitial cells or fibrosis in intractable tumors, as occurs in pancreatic or scirrhous stomach cancer, tend to impede nanoparticle delivery. Thus, it is critical to optimize the type and size of nanoparticles to reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 309 publications
0
41
0
Order By: Relevance
“…1 By combining both therapeutic and diagnostic properties in one single platform, theranostic systems are emerging medical tools that hold great promises in enhancing the therapeutic outcome of cancer therapy. [2][3][4][5] Unlike conventional approaches, the theranostics integrates specific molecular targeting, therapeutic activity, and imaging in one multifunctional medical system, very often based on the use of nanosized carriers. Some of the most attractive features of the nanoparticle-based theranostics include the opportunity to specifically deliver different pharmaceutically active molecules, to monitor their biodistribution in vivo, and, in some cases, also to control/trigger the release of the drug at the target site.…”
Section: Introductionmentioning
confidence: 99%
“…1 By combining both therapeutic and diagnostic properties in one single platform, theranostic systems are emerging medical tools that hold great promises in enhancing the therapeutic outcome of cancer therapy. [2][3][4][5] Unlike conventional approaches, the theranostics integrates specific molecular targeting, therapeutic activity, and imaging in one multifunctional medical system, very often based on the use of nanosized carriers. Some of the most attractive features of the nanoparticle-based theranostics include the opportunity to specifically deliver different pharmaceutically active molecules, to monitor their biodistribution in vivo, and, in some cases, also to control/trigger the release of the drug at the target site.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the MRI results indicated that Gd‐P‐ABs exhibited aggregation‐enhanced MRI capacity when FA‐ Gd BSA was self‐assembled via the chelation effect of Gd 3+ . Such a phenomenon should be explained that more Gd 3+ integration increased the local concentration of Gd 3+ and lowered the molecular tumbling rate of FA‐ Gd BSA (Figure c,d) …”
Section: Resultsmentioning
confidence: 94%
“…Such a phenomenon should be explained that more Gd 3+ integration increased the local concentration of Gd 3+ and lowered the molecular tumbling rate of FA-Gd BSA (Figure 2c,d). [37,38] Afterward, the photothermal effect was then evaluated. Due to the incorporation of IR-780 dye into the structure of Gd-P-ABs, photo-heat conversion efficiency was prior evaluated by monitoring the temperature changes under laser irradiation.…”
Section: Self-assembly and Characterization Of Gd-p-absmentioning
confidence: 99%
“…Imaging MRI is a non-invasive technique widely used in clinical diagnosis. It provides high contrast in soft tissue, threedimensional information and spatial resolution of 20-50 μm for small animals [73]. In recent decades paramagnetic and superparamagnetic nanoparticles have been routinely used as contrast agents to improve the sensitivity of MRI [74].…”
Section: Cell Targetingmentioning
confidence: 99%